Primed for death: Tigray genocide: a survivor's story - Gebrewahid, Goitom Mekonen (Great Britain: Amazon, 2022)
"Have you heard of the Tigray Genocide? Most likely have not. Since November 2020, this genocidal war has already resulted in the deaths of more than half a million civilians and decimated the entire region. With the complicity of the United States, the Ethiopian government is annihilating its own people, along with its ally Eritrea and supplied with cutting-edge lethal weapons such as drones from Turkey, the United Arab Emirates, Iran, Israel, China, and Russia, just to name a few. Both as a victim and survivor of this war, I devoted myself to writing "PRIMED FOR DEATH - Tigray Genocide: A Survivor's Story," detailing my personal experiences as Tigray and its people are forced to defend themselves from a catastrophic genocidal war. My account is not a comprehensive assessment and exploration of the ongoing genocidal war. Rather, it is a collection of my personal experiences and observations of the events that have taken place from early November 2020 until the book’s release."--Amazon.com.
Foreword / by Alex de Waal -- The Aksum massacre -- I've lost a piece of me -- The tale of three generations -- 96 hours in prison -- City of horror -- Love before and during the war.
Includes bibliographical references.
Keywords: Mekonen, Goitom; Genocide -- Ethiopia -- Tigray Region; Ethiopia -- Biography; Autobiographies; Autobiographies